Library and Information Science Education in the face of the Information Society challenge (Información, cultura y sociedad, 2004)
Throughout history, it took agriculture years to develop, to expand, and become known to most cultures. During the last 200 years, part of the humankind has been dominated by the industrial activity. While the rest of the world struggles to participate in the Industrial Revolution, some countries go through a stage that transforms everything in an extraordinarily fast way. It is what is known as “information society”. There is no doubt that society is entering a new era in which each aspect of people lives is characterized by the application of Information and Communication Technologies (ICT). This article presents some changes that must take place in the education of library and information science professionals in this new environment